PERAN MANAJEMEN PENGELOLAAN DOKUMEN PADA PENYELENGGARA UMRAH DI PT. AN NAHL MALANG - Febrianti, Trisna Wahyu Endang; Hidayatullah, Syarif; Rachmadian, Aprilia (Multazam : Jurnal Manajemen Haji dan Umrah, 2023)
Hajj documents are data consisting of the identity of pilgrims used to complement or fulfill the requirements of the pilgrimage. Hajj documents consist of a passport that includes a visa. In addition to passports accompanied by visas used in Saudi Arabia, it is required for regular pilgrims to wear the identity or identity of the pilgrims in the form of an identity bracelet. The type of method in this research is descriptive qualitative research, using management theory. Researchers collected data using interviews, observation and documentation. The results obtained in this study stated that Travel An Nahl Hajj and Umrah used a professional management system according to procedures according to the Decree of the Minister of Religion that had been stipulated. From the results of research using qualitative methods, the results obtained were that the management of Umrah documents was carried out in accordance with the implementation of a management information system with a structured database system, so that data on pilgrims who would, are currently or have already carried out Umrah using the services of PT. An Nahl Malang will be well recorded.